EXAMINATIONS IN AUDITING. - Littleton, A. C. (The Accounting Review, 1943)
Abstract In this article the author presents an interpretive observation of the examination questions in auditing. He analyses, whether the examination questions changed as auditing has developed during the past forty-five years. According to the author, the observation of the studies conducted in this field shows the tendency for questions on auditing procedure to grow less prominent. Auditing theory and non-auditing questions increase. The ranking of question types in these studies also provide some suggestions of the change. The first ranking item in the earlier period was number ten in the list for the lastest period, the second later became fifth, the third was seventh, the fourth practically disappeared later, the fifth item became fourth, and the sixth became eleventh. It is clear in the studies that changes are taking place. Broad general questions on the nature and purpose of auditing are of late being replaced by questions that are more pointed and specific. Earlier auditing examinations made frequent use of questions on the theory of accounts. The trend has been away from this type of theory question and toward theory as it involves accounting statements.